X = 3z - 22
z = 6
5x + 4y + 3z = 14
5 (3z - 22) + 4y + 3 (6) = 14
15z - 110 + 4y + 18 = 14
15 . 6 - 110 + 4y + 18 = 14
90 - 110 + 4y + 18 = 14
90 - 110 + 18 - 14 + 4y = 0
-16 + 4y = 0
4y = 16
y = 4
Answer:
In order for the appropriate answer to be given, you need to include the original measurements as well.
Answer: the equations are
k = d + 33
k - 2 = 4(d-2)
Step-by-step explanation:
Let the present age of Kevin be represented by k
Let the present age of Daniel be represented by d
Kevin is 33 years older than Daniel. This means that the expression for their current age is
k = d + 33
Two years ago, Kevin was 4 times as old as Daniel. This means that 2 will be subtracted from their present ages to depict two years ago. Therefore, Two years ago for Daniel will be d-2
Two years ago for Kevin will be k - 2
Remember that Kevin was 4 times as old as Daniel two years ago, it becomes
k - 2 = 4(d-2)
Answer:
980 hers your proof so 170 * 7 =180
Step-by-step explanation:
Answer:
a) 46.98%
b) increasing rate of change
Step-by-step explanation:
In year 1987, investment worth $29800
In year 1997, investment worth $43800
Rate of change = 1997investment - 1987investment / 1987investment × 100
Rate of change = 43800 - 29800/29800 × 100
= 14000/29800 × 100
= 0.46979 × 100
= 46.98%
Therefore, the rate of change of the investment during the time period is 46.98%.
b) The rate of change of the investment is increasing. This is as a result of the following reasons. First, the value of rate of change is positive. Second, there is no value for rate of change for period before the time period so we cannot compare rate of change.